Tingkat Pendidikan dan Pengetahuan Kepala Keluarga Tentang TB Paru di RT 03 RW 07 Kelurahan Pematang Reba, Wilayah Kerja Puskesmas Pekan Heran, Kabupaten Indragiri Hulu - Yulianto Yulianto (FORIKES, 2020)
Pulmonary tuberculosis (pulmonary TB) is an infectious disease caused by Mycobacterium Tuberculosis, which most commonly affects the lungs. The number of patients with pulmonary TB in Indragiri Hulu Regency in 2017 was 329 patients. Pematang Reba Village is the highest case in Pekan Heran Puskesmas Work Area as many as 16 patients, where RT 03 RW 07 is the highest case of all RTs in Pematang Reba Village. The aim of study is investigate the relationship of education level with the knowledge of the Head of the Family in RT 03 RW 07 Kelurahan Pematang Reba. The study design used descriptive correlation with cross sectional approach. The population in this study is the head of the family. The sampling technique used was simple random sampling with 132 respondents. The results of the univariate test on the level of education of the Head of the family had basic education (48.5%), secondary education (25%), high education (26.5%) and knowledge of TB Lungs are good (33.3%), Sufficient (20.5%), Poor (46.2%). Bivariate test results showed there is relationship between the level of education with the knowledge of family heads about pulmonary TB, with a p value of 0,000 with ɑ